2011
DOI: 10.1007/s10658-011-9785-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in genetic structure and chemotype composition of Fusarium graminearum sensu stricto populations causing wheat head blight in individual fields in Germany

Abstract: Fusarium head blight (FHB) is one of the most destructive diseases of wheat. Twelve small commercial wheat fields (size 1-3 hectares) were sampled in Germany for Fusarium populations at three spots per field with 10 heads each. PCR assays using generic primers confirmed 338 isolates as F. graminearum sensu stricto (s.s.) (64.9%) out of 521 Fusarium spp. that were further analyzed. Populations of F. graminearum s.s. in Germany contain three types of trichothecenes with a dominancy of 15-acetyldeoxynivalenol che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 40 publications
10
57
0
Order By: Relevance
“…The present work is the first study of FGSC species diversity in Norway. All FGSC isolates collected from Norwegian cereals were identified as F. graminearum, which is consistent with previous evidence that F. graminearum is the dominant species within this species complex in Europe (Laday et al 2004;O'Donnell et al 2004;Toth et al 2005;Yli-Mattila et al 2009;Talas et al 2011;Boutigny et al 2014). F. graminearum is also dominant in the United States and Canada (Starkey et al 2007;Gale et al 2007;Ward et al 2008;Schmale et al 2011), and is found on all continents with the exception of Antarctica (O'Donnell et al 2004;Aoki et al 2012;Backhouse 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present work is the first study of FGSC species diversity in Norway. All FGSC isolates collected from Norwegian cereals were identified as F. graminearum, which is consistent with previous evidence that F. graminearum is the dominant species within this species complex in Europe (Laday et al 2004;O'Donnell et al 2004;Toth et al 2005;Yli-Mattila et al 2009;Talas et al 2011;Boutigny et al 2014). F. graminearum is also dominant in the United States and Canada (Starkey et al 2007;Gale et al 2007;Ward et al 2008;Schmale et al 2011), and is found on all continents with the exception of Antarctica (O'Donnell et al 2004;Aoki et al 2012;Backhouse 2014).…”
Section: Discussionsupporting
confidence: 89%
“…The 3- isolates belonging to population 2 were included in the analysis of aggressiveness, ten of these were included in the growth rate analysis c 17 3-ADON isolates were included in the analysis of aggressiveness, 16 of these were included in the growth rate analysis ADON chemotype also predominated among a small set of FGSC isolates from an earlier collection of Norwegian cereals (Langseth et al 1999(Langseth et al , 2001, and was found in oat and wheat samples collected between 2009 and 2011 in Sweden, whereas the 15-ADON chemotype was not observed (Fredlund et al 2013;Lindblad et al 2013 (Nielsen et al 2012). Our data add to a growing set of studies indicating a geographical partitioning of trichothecene types (chemotypes or genotypes) throughout Europe, with 3-ADON dominating in Northern Europe, whereas 15-ADON appears predominant in the Western and Southern Europe including the UK (Jennings et al 2004), Belgium (Audenaert et al 2009), Italy (Prodi et al 2009;Somma et al 2014), Luxembourg (Pasquali et al 2010), Poland (Stępień et al 2008), Hungary (Toth et al 2005), Germany (Talas et al 2011), and France (Boutigny et al 2014). …”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Such a deletion is present in all isolates of F. culmorum tested to date (Chandler et al 2003;Kammoun et al 2010), but it is rather rare in F. graminearum (Lee et al 2001;Chandler et al 2003). Our results are consistent with the chemotype screenings from Eastern Europe, where 15-ADON chemotype dominates (Prodi et al 2009;Talas et al 2011), whereas 3-ADON chemotype is more frequent in Northen Europe (Jestoi et al 2008). The present samples included no NIV producing isolates.…”
Section: Resultssupporting
confidence: 88%
“…The present samples included no NIV producing isolates. Talas et al (2011) also detected only 1.2% NIV producing isolates in neighbouring Germany, although low to medium frequencies of this chemotype have been recorded in Europe (Stepien et al 2008;Audenaert et al 2009;Prodi et al 2009). The analysis of a larger collection of Czech F. graminearum isolates would probably reveal a frequency of NIV producers that comparable to detected in Germany.…”
Section: Resultsmentioning
confidence: 89%